World Economic and Financial Surveys, Primary Commodities, 1988 : Primary Commodities. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1988)
This paper provides an analysis of recent developments relating to the major nonfuel primary commodities traded in international markets. Particular attention is given to market price movements and the factors underlying these movements. A number of adjustments in the international trading environment in which commodity prices are determined occurred in 1987, and even more significant changes are expected in the years ahead. Some of the adjustments in the past year affected only bilateral trading arrangements, while others, such as certain initiatives undertaken in the Uruguay Round of the General Agreement on Tariffs and Trade (GATT) negotiations and those relating to some international commodity agreements were of a multilateral nature. The present round, the eighth in a series of GATT negotiations held since 1947, involves two elements that are of particular relevance to international trade in commodities. Although only small changes were made in 1987 in the various multilateral schemes that exist to compensate countries for export earnings shortfalls, a significant increase in such financing in 1987 had the effect of stabilizing many developing countries' export earnings, thereby maintaining their capacity to import and buoying world trade.